What light does Matthew"s use of Mark in Matthew 1–4 throw on Matthew"s theological location? - Loader, William R. G. (HTS teologiese studies, 2016)
This article approaches the issue of Matthew’s theological context by examining Matthew’s use of Mark, including through redaction and supplementation, in Matthew 1–4. This is undertaken in two parts: Matthew 1–2, which is largely additional material, and Matthew 3–4, followed by a concluding assessment. Issues addressed or alluded to in these chapters frequently find resonance in the remainder of Matthew’s gospel and so give important clues about Matthew’s concerns and their relevance for understanding its context. Such issues include the importance of messiahship; continuity with Israel, but also with John the Baptist and the Church; defence against slander; heightened christological claims; soteriology; Gentile mission; the status of Torah; and Jesus as judge to come. The article suggests a location within a Jewish religious context with a Jewish self-understanding, separate from the synagogue, but claiming to belong where its opponents would claim it did not; and a Christian tradition where the approach of ‘Q’ to Torah is upheld in contrast to Mark’s, while embracing and expanding Mark’s Christology and restoring the common understanding of Gentile mission as a post- Easter phenomenon.